How Japan’s know-how can help address Africa’s food and nutrition challenges Interventions and impacts - Yamauchi, Futoshi (2022)
Futoshi Yamauchi The 8th Tokyo International Conference on African Development (TICAD8) Side Event: How Japan’s know-how can help address Africa’s food and nutrition challenges: Interventions and impacts SEP 28, 2022 - 6:00 TO 7:30PM JST